Oil Wealth and Economic Behavior : Case of Venezuela 1966-1981. (IMF Working Papers; Working Paper, 1988)
A short-run macroeconomic model is estimated for Venezuela, in order to examine the hypothesis that the availability of oil resources may entail a confidence effect-on perceived future incomes-that influences the expenditure and portfolio behavior of economic agents. Such confidence effect is found to be empirically significant. Model simulations reveal that the impact of oil price changes on the level and variability of money demand, balance of payments and inflation are significantly more pronounced in the presence of the confidence effect than in its absence. This has significant implictions for the size and structure of the needed policy interventions.